Teacher Profile and Needs Analysis in Learning Digital Ad Text Writing - Eka Malinda Rahmawati; Khaerudin Kurniawan; Isah Cahyani (Universitas Muhammadiyah Malang, 2025)
Digital transformation in education requires Indonesian teachers to have high digital literacy competencies, including teaching digital advertising text genres. However, the reality is that there are still many teachers who are not ready in terms of pedagogical, technological, and learning content. This study aims to describe in depth the profile and needs of Indonesian teachers in learning to write digital advertising texts. The research uses a qualitative approach with an exploratory case study design. Data was collected through in-depth interview techniques, classroom observations, and analysis of teaching equipment documentation, with participants as many as 50 Indonesian teachers at the junior high school level in the Bandung area. The study results show that most teachers have not mastered the essential elements of digital advertising texts, such as persuasion aspects, visual elements, and digital platforms as teaching media. Teachers' needs include technical training in writing digital advertisements, developing contextual digital teaching media, and learning evaluation guidelines. These findings reinforce the need to create TPACK-based training programs tailored to the local context and today's digital literacy challenges. This study also confirms that teachers' unpreparedness is not the result of a lack of motivation but limited access, experience, and systemic support. In conclusion, there is an urgent need to design policy interventions and professional development programs to bridge the teacher competency gap in learning to write digital advertising texts effectively and sustainably.